Super-Enhancers and CTCF in Early Embryonic Cell Fate Decisions - Agrawal, Puja; Rao, Sridhar (Frontiers in Cell and Developmental Biology, 2021)
Cell fate decisions are the backbone of many developmental and disease processes. In early mammalian development, precise gene expression changes underly the rapid division of a single cell that leads to the embryo and are critically dependent on autonomous cell changes in gene expression. To understand how these lineage specifications events are mediated, scientists have had to look past protein coding genes to the cis regulatory elements (CREs), including enhancers and insulators, that modulate gene expression. One class of enhancers, termed super-enhancers, is highly active and cell-type specific, implying their critical role in modulating cell-type specific gene expression. Deletion or mutations within these CREs adversely affect gene expression and development and can cause disease. In this mini-review we discuss recent studies describing the potential roles of two CREs, enhancers and binding sites for CTCF, in early mammalian development.